Comparison of clinical features between patients with bone and soft tissue fibrosarcomas. Issue 7 (8th August 2022) - Matsuoka, Masatake; Onodera, Tomohiro; Yokota, Isao; Iwasaki, Koji; Hishimura, Ryosuke; Suzuki, Yuki; Kondo, Eiji; Iwasaki, Norimasa
Abstract: Background and Objectives: Fibrosarcomas predominantly arise in soft tissues, but can also develop in bone. Because of their rarity, whether bone development has an impact on clinical features has not been addressed. Methods: We included fibrosarcoma patients diagnosed between 1983 and 2016 in the Surveillance, Epidemiology, and End Results database. Differences in clinical features between fibrosarcoma of bone (FS‐B) and fibrosarcoma of soft tissue (FS‐ST) were investigated. Results: After excluding patients without information regarding cause of death, site of origin, distant tumor or survival, 1443 patients were included. Of those, 98 patients had FS‐B. Patients with FS‐B were younger, more frequently male, with fibrosarcomas that more often developed in an extremity and were histologically high‐grade. In contrast, no difference in potential to metastasize was observed. Survival was almost equal between FS‐B and FS‐ST (FS‐B/FS‐ST: cancer‐specific survival, hazard ratio [HR]: 1.2, 95% confidence interval [CI]: 0.8–1.7; overall survival, HR: 1.3, 95% CI: 0.9–1.7). Conclusions: Our results clearly indicated that patient backgrounds differed, such as younger age and greater tendencies to affect males, develop in an extremity and show high‐grade tumor in patients with FS‐B. In contrast, no differences were observed in distant metastatic potential or survival.